2021
DOI: 10.3390/plants10112357
|View full text |Cite
|
Sign up to set email alerts
|

Transient Waterlogging Events Impair Shoot and Root Physiology and Reduce Grain Yield of Durum Wheat Cultivars

Abstract: Durum wheat (Triticum turgidum L. subsp. durum (Desf.) Husn) is a staple crop of the Mediterranean countries, where more frequent waterlogging events are predicted due to climate change. However, few investigations have been conducted on the physiological and agronomic responses of this crop to waterlogging. The present study provides a comprehensive evaluation of the effects of two waterlogging durations (i.e., 14 and 35 days) on two durum wheat cultivars (i.e., Svevo and Emilio Lepido). An integrated analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 54 publications
1
25
0
1
Order By: Relevance
“…Leaf pigments and stomatal conductance were decreased in both genotypes under salinity due to degradation of chlorophyll molecules caused by overproduction of ROS and replacement of K by Na ions and up-regulation of chlorophyllase activity [ 3 , 37 ]. These physiological changes also occur in response to other abiotic stress in wheat including waterlogging [ 38 ] and heat stress [ 39 ]. Salt induced damage to pigments was relieved under the application of K alone or in combination with HA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf pigments and stomatal conductance were decreased in both genotypes under salinity due to degradation of chlorophyll molecules caused by overproduction of ROS and replacement of K by Na ions and up-regulation of chlorophyllase activity [ 3 , 37 ]. These physiological changes also occur in response to other abiotic stress in wheat including waterlogging [ 38 ] and heat stress [ 39 ]. Salt induced damage to pigments was relieved under the application of K alone or in combination with HA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many other studies have reported salt induced excessive production of ROS [ 18 , 33 ]. Closure of stomata due to dissociation of electron transport chain is the main reason for salt induced oxidative stress [ 37 , 38 , 39 , 40 ]. Lipid peroxidation activates K efflux channels causing the leakage of K [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, plant survival ( Wu et al, 2017 ), recovery, and plant biomass ( Ploschuk et al, 2017 ) are considered for screening waterlogging-tolerant genotypes in different crops. The recovery after stress involves the distribution of the carbon to roots after waterlogging stress and hypoxia conditions to enhance root growth and to reestablish a root-to-shoot ratio during the recovery phase ( Cotrozzi et al, 2021 ). High plant mortality among sensitive genotypes under waterlogged conditions may be attributed to anoxic conditions created by waterlogging.…”
Section: Discussionmentioning
confidence: 99%
“… Pan et al (2021) also reports that the plants could maintain energy production through glycolysis and ethanol fermentation under waterlogged conditions; however, prolonged waterlogging leads to the accumulation of toxic substances and reactive oxygen species, which causes cell death and plant senescence. The pigment degradation affects the photosynthetic activity results in the slow-down of the crop growth, which directly affects the yield ( Cotrozzi et al, 2021 ). Inhibition of plant growth and development is also reported in sensitive genotypes of field bean ( Pociecha et al, 2008 ), tomato ( De Ollas et al, 2021 ), and mung bean ( Ahmed et al, 2002 ; Kumar et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, plant responses upon recovery and the reoxygenation process, or priming, have been less examined than those conferring tolerance during the stress period [1,8]. The analysis of response of root in wheat [9] and in oat [10] revealed that the recovering differed between genotypes and the physiological damages could be stronger in root tissue than in shoots. Priming could be defined as the process which occurs after pre-exposure of plants to a stress factor, resulting in "stress memory", i.e., preparing plants to respond to secondary stress events.…”
Section: Introductionmentioning
confidence: 99%